Determining Body Height Based on The Middle Finger Length (III digit of Manus) - Kristin Sihaloho, Asan Petrus (Journal of Medical Care Research and Review, 2022)
Introduction: Various kinds of events such as mass disasters or murder by mutilation can cause a person’s limbs to be unrecognizable and even body parts to separate. Thus, estimating height is a major step in the process of identifying an unknown person. Research on the fingers is important to do to determine a person’s identity because the pieces of bodies found are not always in the form of long bones; they can also be found in the form of short pieces such as fingers. Objectives: This study aims to determine the relationship between the length of the middle finger and the height of the members of the police force in the Medan-Sunggal sector in 2021. Methods: The design of this study was analytic correlation with a cross-sectional approach. The population of this study is male and female citizens aged 23 to 58 years who are members of the Sunggal Medan Police Sector in 2021 who meet the inclusion and exclusion criteria. The sampling technique used the total sampling method and amounted to 90 people. Results: The length of the middle finger has a positive and significant correlation with height, with a correlation coefficient ranging from 0.780 to 0.939 (p<0.001). The linear regression equation obtained shows the Standard Error of the Estimate (SEE) which ranges from 1.714 to 3.528 (p<0.001). Conclusion: There is a significant relationship between the length of the middle finger (digit III manus) and the height of the members of the Sunggal Medan Police in 2021 with a strong to very strong correlation coefficient, thus height can be estimated by measuring the length of the middle finger of the hand through the equation linear regression. Keywords: Middle finger length, height, linear regression equation, Anthropometry.